1442. Pneumonia Hospitalizations Averted With 13-Valent Pneumococcal Conjugate Vaccination of Adults Aged 18–64 Years With Diabetes in the United States. (26th November 2018) - Suaya, Jose; Gessner, Bradford D; Chilson, Erica; Vojicic, Jelena; Swerdlow, David L; Isturiz, Raúl E; McLaughlin, John M
Abstract: Background: Diabetes, a prevalent chronic condition in younger adults, increases the risk of pneumonia. The incidence of pneumonia hospitalization among adults aged < 65 years with diabetes is comparable to that of the overall population aged ≥65 years. While 13-valent conjugate pneumococcal vaccination (PCV13) is routinely recommended for adults aged ≥65 years, it has not been recommended for younger adults with diabetes. We modeled the potential impact of PCV13 use in this population. Methods: We estimated the cumulative number of pneumonia hospitalizations and hospital days potentially averted with PCV13 use in adults aged < 65 years with diabetes over 5 years in the United States. Model inputs are summarized in Table 1. We ran multiple scenarios depending on a number of vaccine efficacy/effectiveness (VE) estimates. We estimated the number of hospitalizations averted as the product of (i) the size of the target population, (ii) the incidence of all-cause CAP, (iii) the proportion of CAP that is PCV13 type, (iv) PCV13 effectiveness, and (v) the duration of protection for PCV13 over a 5-year time horizon. Number-needed-to-vaccinate (NNV) for each scenario was also assessed. Results: Roughly 15 million adults aged < 65 years have diabetes in the United States, accounting for about 250, 000 pneumonia hospitalizations annually. Based on published, US estimates of pneumonia incidence and PCV13 etiology, PCV13 vaccination in this population could avert 24, 638–44, 506 hospitalizations and 206, 955–373, 854 hospital days over a 5-year period. NNV to avert one hospitalization and one hospital day were 344–622 and 41–74, respectively. Conclusion: PCV13 vaccination of younger adults with diabetes could reduce a substantial number of pneumonia hospitalizations. NNV is comparable to those for adults aged ≥65 years, for whom PCV13 is currently recommended. Disclosures: J. Suaya, B. D. Gessner, E. Chilson, D. L. Swerdlow, J. M. McLaughlin: Pfizer Inc.: Employee and Shareholder, Salary. J. Vojicic, Pfizer: Employee and Shareholder, Benefits and stock and Salary. R. E. Isturiz, Pfizer: Employee and Shareholder, Benefits and stock and Salary.